The The Utilization of Online Dating Application in College Student : Research Journal for Midterm Asessment Tasks, Communication Science Study Program (INTEGRATION PROCEEDING, 2023)
In this digital era, the internet has grown rapidly in influencing people's patterns and behavior. The use of the internet provides many benefits and even impacts that are generated by the community itself such as online dating applications. Some people, especially the Gen Z generation, may already be familiar with the online dating application. Because it is enough with a smartphone this application can help us find a partner online. Downloadable apps like Tinder, Litmatch and Tantan. These applications have many users and are proven to provide many friends and even partners to communicate. The purpose of this study is to prove how effective online dating applications are among digital people who are looking for friends or partners. In addition, online dating applications have become popular among the public, especially teenagers and people who are looking for a partner. The method used is a combination of quantitative and qualitative by analyzing the results of the questionnaire and collecting information data from the informants. The results obtained indicate that most of the respondents stated that online dating applications are able to provide a more pleasant means of communicating and also not boring because the features provided are interesting. The conclusion obtained from this study is that online dating applications are only used when someone feels bored and fills their spare time to play online dating applications. In addition, they also want to add relationships about new friends or partners whose reach is wider.